Responsabilidad civil derivada de daños sufridos por futbolistas en encuentros deportivos - Reyna Mantilla, Renato Alejandro (2017)
This research entitled "CIVIL LIABILITY DERIVED FROM DAMAGES SUFFERED BY SOCCER PLAYERS IN SPORTS ENCOUNTERS", has as main purpose to know what are the budgets and requirements for a player, who has been damaged by an opponent in the development of a football match, Has the power to go to the respective court with the objective of receiving compensation for the damage suffered. The investigation is based on the various actions of soccer players who are reflected in serious injuries to their opponents; In fact, it seeks to have knowledge if it is feasible the existence of civil liability in the framework of the development of a football match of a professional nature. In view of this, as the existence of the budgets provided for determining a civil liability on the part of the players results, the present investigation also seeks to develop the right of an injured athlete to claim full compensation for the damages suffered. It should be specified that it is devoid of any disciplinary sanction determined by the regulations corresponding to the sport of football. Finally, according to the results, conclusions and recommendations of the present, based on the case study to be studied also, an investigation is planned according to the objectives set out in the beginning